THE STATUS OF EVIDENCE PROCEEDS OF CRIME IN GENERAL AND MILITARY CRIMES - IRMAN PUTRA; ARIEF FAHMI LUBIS (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Determination of the status of evidence of crimes in military courts has the same legal implications as in general courts. Based on the provisions of Article 191 of Law 31 of 1997 concerning Military Courts, it is stated that "In the case of a sentencing decision or being free from all charges or acquittal from all legal charges, the Court stipulates that the confiscated evidence be handed over to the party most entitled to receive it back whose names are listed in the the decision, except if according to the provisions of the legislation, the evidence must be confiscated for the benefit of the state or destroyed or damaged so that it cannot be used anymore", but when the court decides that the evidence is returned to the rightful person, it often issues a decision that raises the question of who is entitled to it. . The purpose of this study is to analyze using the approach method used in this study is a juridical approach by conducting a comprehensive study based on laws and regulations and also empirical juridical research, namely conducting an assessment based on observations of several court decisions which until now have not been able to return of evidence to the rightful person. The results of this study indicate that according to the procedural law applicable in the Military Courts and general courts, it is necessary for the judge to confirm in the court's decision by stating who has the right so that there is legal certainty.